Uji Komparasi Abnormal Return, Trading Volume, Dan Trading Frequency Sebelum Dan Sesudah Peristiwa Share Split Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010 – 2013: Periode Pengamatan 15 Hari Sebelum dan Sesudah Share Split - Vincent, Jordan; Kurnia, Ratnawati (Ultimaccounting Jurnal Ilmu Akuntansi, 2014)
This study is event study that was conducted to determine differences in abnormal returns, trading volume, and trading frequency before and after the events of the share split. The object of this research is the companies that did the share split and listed in Indonesia Stock Exchange in 2010 - 2013. Samples were taken by using purposive sampling as many as 24 companies. The criteria is the company did not do corporate action right issue, pre-emptive rights, a share dividend and bonus shares in the same year with share split, then the company share actively traded 15 days before and after the share split. Data analysis technique begins with a test of normality using Kolmogorov - Smirnov test, then test the hypothesis using a paired t test to compare the differences before and after share split. In testing the hypothesis showed that the difference was only found on variable trading frequency before and after share split. While the other variables are abnormal return and trading volume was not found significant differences before and after the share split. Keywords: Share split, abnormal returns, trading volume, trading frequency